2010
DOI: 10.1007/s11199-010-9855-6
|View full text |Cite
|
Sign up to set email alerts
|

Child Sexual Abuse History and Feminine Gender-Role Identity

Abstract: The association between child sexual abuse (CSA) and feminine gender-role identity was examined among 75 women with and 107 without a history of CSA. Undergraduates and hospital employees from a university in the Southern United States completed questionnaires on the internet. Three aspects of feminine identity were assessed, including how much participants identified with feminine versus masculine traits, endorsed stereotypes about women, and viewed themselves as meeting feminine self-standards. Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…Examination of correlations between GRS and childhood sexual trauma, although indicating a significant association in the nonclinical group, consistent with previous research suggesting that childhood sexual abuse may sensitize survivors to sociocultural messages regarding normative femininity (Krause & Roth, ), failed to show any effect in the clinical group. Although it is not entirely clear why this should be the case, it is possible that low within‐group variance was responsible.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Examination of correlations between GRS and childhood sexual trauma, although indicating a significant association in the nonclinical group, consistent with previous research suggesting that childhood sexual abuse may sensitize survivors to sociocultural messages regarding normative femininity (Krause & Roth, ), failed to show any effect in the clinical group. Although it is not entirely clear why this should be the case, it is possible that low within‐group variance was responsible.…”
Section: Discussionsupporting
confidence: 84%
“…3 In the light of research suggesting a relationship between GRS and child sexual abuse (CSA; Krause & Roth, 2011;Krugman, 1995;Lebowitz & Roth, 1994;Lisak, 1994) and the well-documented links between CSA and psychosis (Varese et al, 2012), we hypothesize that GRS will be associated with a history of CSA.…”
Section: Purpose Of the Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that we also found an association between a masculine gender role and childhood sexual abuse with our sample. Recent research with adult (presumably heterosexual) women has found mixed results, with one study finding that those with a childhood sexual abuse history were more likely to identify with feminine rather than masculine traits (Krause and Roth 2011), and another finding the opposite (McMullin et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…D'Augelli, Grossman, and Starks (2006) also examined the role of gender atypicality in female children and found 66% of the sample of lesbian and bisexual youth reported greater verbal and physical victimization than those not reporting gender atypicality. However, additional research involving identification with feminine or masculine traits and resulting levels of abuse has resulted in mixed findings (Krause & Roth, 2011;McMullin, Wirth, & White, 2007). Further research regarding traits which may predispose children who later identify as lesbian to occurrences of physical abuse is thus further warranted to fully examine effects of sexual identification traits apparent at the individual system level beginning in childhood.…”
Section: Factors Of Abusementioning
confidence: 99%